2011
DOI: 10.1099/ijs.0.024166-0
|View full text |Cite
|
Sign up to set email alerts
|

Description of Actinomycetospora chibensis sp. nov., Actinomycetospora chlora sp. nov., Actinomycetospora cinnamomea sp. nov., Actinomycetospora corticicola sp. nov., Actinomycetospora lutea sp. nov., Actinomycetospora straminea sp. nov. and Actinomycetospora succinea sp. nov. and emended description of the genus Actinomycetospora

Abstract: Eight actinomycete strains that form bud-like spore chains were isolated from various samples collected in Japan. Phylogenetically, the isolates formed a single clade with the type strain of Actinomycetospora chiangmaiensis according to 16S rRNA gene sequence analysis. The isolates contained meso-diaminopimelic acid, d-glutamic acid and d- and l- alanine in the cell-wall peptidoglycan, arabinose and galactose as characteristic sugars, phosphatidylcholine and phosphatidylethanolamine as diagnostic phospholipids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…Interestingly, the previously reported Actinomycetospora species were mainly isolated from subtropical/tropical region. 9,10 A similar tendency was also reported by González et al 3 It is considered that the abundance or diversity of Actinomycetospora correlated to the climate. However, ecological futures of lichenassociated actinomycetes, including Actinomycetospora were not clarified yet.…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…Interestingly, the previously reported Actinomycetospora species were mainly isolated from subtropical/tropical region. 9,10 A similar tendency was also reported by González et al 3 It is considered that the abundance or diversity of Actinomycetospora correlated to the climate. However, ecological futures of lichenassociated actinomycetes, including Actinomycetospora were not clarified yet.…”
Section: Resultssupporting
confidence: 80%
“…The 16S rRNA gene sequence similarities to members of the genus Actinomycetospora ranged from 97.0 to 98.4%. [8][9][10] The phylogenetic tree constructed with 16S rRNA gene sequence data of members of the genus Actinomycetospora and related genera using the neighbor-joining method showed that strain IR73-Li102 T formed a monophyletic clade with A. chiangmaiensis, A. corticola and A. rishiriensis (Figure 1). Moreover, this clade was strongly supported by the maximum-likelihood and maximum parsimony trees with high bootstrap values.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The genus Actinomycetospora was first established by Jiang et al (2008) and its description was later emended by Tamura et al (2011b) and Zhang et al (2014). At the time of writing, the genus encompasses 11 species with validly published names (http://www.bacterio.net/actinomycetospora.html), including the recently described Actinomycetospora atypica (Zhang et al , 2014).…”
mentioning
confidence: 99%